Value vs. Price in Real Estate Valuation in Times of Uncertainty - Dariusz KLOSKOWSKI; Beata KLOSKOWSKA (Communications of International Proceedings, 2025)
When considering the relationship between value categories and real estate prices in times of uncertainty, it is undoubtedly important to recognize that the analysis of the real estate market, its area and segregation, and ultimately the impact of external stimuli that disrupt its rhythm, is crucial. This stems from the fact that market assets, i.e., real estate, significantly influence the economic development of each country. A significant gap has been noted in the literature on the subject, revealing a lack of consideration for threats resulting from diagnosed risks on real estate value. This essentially concerns real estate valuation, i.e., the mathematical approach to assessing real estate value, where threats are not assigned attributes and their value is not assessed. This is also evident in the literature review, which is sparse on the impact of threats, primarily those related to globalization, which can significantly impact the final real estate valuation. Therefore, it was deemed appropriate to attempt to identify a solution to optimize valuation, taking into account the state of threats to the property being valued. The main purpose of this article is to present the value and price of real estate in the real estate valuation process in the context of initiating potential risks arising from operating in times of uncertainty. The research problem in this article is formulated as the question: „In today's times of uncertainty, should various types of risks be considered in real estate valuation, as they constitute a threat element that significantly influences the final valuation?” The study's research hypothesis is formulated as follows: "Different types of real estate risks should reflect the threat variable in their design, which influences the final valuation of real estate." The study utilized secondary analysis of literature and legislative data in Poland and the European Union, allowing for an analysis of available definitions of location, including how it is incorporated into real estate valuation procedures, with particular emphasis on the directionality of application in appraisers' valuation reports. The use of a case study approach allowed for the use of an econometric model for real estate valuation that takes into account various types and categories of risks, assuming the continued operation of the real estate market under conditions of uncertainty. The study outlines recommendations and conclusions related to the need to consider threats and risks not only in linear decision-making models under uncertainty, reflecting the state of threat, but also in situations where basic approaches are used in real estate market value valuation.
Keywords: real estate valuation; price; market threats; investment risk